Identification Of Risk Sources And Corrective Actions For Cost Overrun In The Management Of Subcontractors For The Rimp Los Package 03 Project In Indramayu, West Java - Eko Prasetyo; Erni Yulianti; Grace Citra Dewi (Publikasi Indonesia, 2023)
This research examines the sources of cost overrun risk in construction project management, focusing on the Range Irrigation Modernization Project (RIMP) LOS Package 03 in Indramayu, West Java. Through data analysis and literature review, major risk sources are identified, including inadequate supervision of subcontractors, subcontractor inability to complete tasks on schedule, and poorly coordinated design changes. Additionally, environmental project factors, such as unpredictable weather conditions and project site accessibility, are analyzed. The findings contribute to understanding project management practices and provide corrective action guidelines to mitigate cost overrun risks.